STEAM and theatrical education - Jefferson Rodrigues-Silva; Ángel Alsina (Universidade Nove de Julho, 2024)
Eleven mechanical engineering students participated in a STEAM (interdisciplinarity between Science, technology, engineering, Arts/Humanities, and Mathematics) drama activity of conceiving and performing a play which addressed their course. Following, we pursued a Thick Description of this project, including the meanings and intentions of the play. Accordingly, we interviewed the students so that this description could reflect their voices. As a result, we observed that the drama activity permitted learning about engineering and theatre. Moreover, it was a space to contrast the ideal and the real engineering toward society and to call students to play the role of subjects responsible for their personal, professional and political lives.